PERFORMANCE, EMISSION AND EFFICIENCY ANALYSIS OF A DIESEL ENGINE OPERATED WITH DIESEL AND DIESEL-ETHANOL (E20) BLEND - Özgür, Tayfun; Tosun, Erdi; Özgür, Ceyla; Tüccar, Gökhan; Aydın, Kadir (MATTER: International Journal of Science and Technology, 2017)
Conventional fossil fuel sources face with scarcity risk. Therefore, researchers are trying to find new renewable alternative energy sources which have potential to replace conventional sources. Alcohol and biodiesel are prominent sources among others. In this study, performance and emission characteristics of a diesel fuel and ethanol added (20% vol.) diesel fuel (E20) operated compression ignition engine was studied in between 1000 - 2600 engine speed. Torque, power, specific fuel consumption curves as performance and carbon monoxide (CO), nitrogen oxides (NOx) curves as emission parameters with respect to engine speed were obtained. Energy and exergy efficiency curves versus engine speed in order to assess the system thermodynamically were also obtained. Results showed that, while torque, power, CO emission were decreased, specific fuel consumption, NOx emission were increased with use of diesel-ethanol blends. On the other hand, both energy and exergy efficiency values were decreased when alcohol was added to diesel fuel